Media Literasi: Upaya Bijak Menyikapi Terpaan Tayangan Televisi - Respati, Wira (Bina Nusantara University, 2013)
The television media have transformed into industry. Tight competition among TV stations demands the media people to provide programs based on the market taste. Therefore, mostly TV stations design and produce their programs based on share and rating numbers, instead of quality. On the other side, TV stations have important roles in constructing social and cultural development. Currently, TV programs are merely produced based on the business orientation so that the quality of the TV programs is often ignored. Audience must be wise and smart to protect themselves from poor-quality TV programs exposure. This can be achieved by improving their Media Literacy. In the end, Audience is no longer treated as passive object, but actively takes control on the content selection.